2014
DOI: 10.1039/c3ra45250f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled nucleation and growth of nanostructures by employing surface modified GaN based layers/heterostructures as bottom layer

Abstract: Controlled nucleation and growth of Zinc oxide nanorods is achieved on GaN, etched GaN and AlGaN/GaN heterostructure bottom layers grown by a metal organic chemical vapour deposition technique. The effects of the bottom crystalline layers on the structural, morphological and optical properties of the as grown ZnO nanorods have been investigated by high-resolution X-ray diffraction, scanning electron microscopy, photoluminescence and Raman measurements. HRXRD (0002) reciprocal-space mapping (RSMs) studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Nowadays, GaN and its related III-nitrides have generated a great deal of interest due to their superior properties, which make them viable for the applications such as light-emitting diodes, laser diodes, eld effect transistors, and photo-detectors. [1][2][3][4][5] As usual, GaN lms are grown by metal-organic chemical vapor deposition (MOCVD). [6][7][8] However, it requires a high growth temperature, which leads to high consumptions in both power and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, GaN and its related III-nitrides have generated a great deal of interest due to their superior properties, which make them viable for the applications such as light-emitting diodes, laser diodes, eld effect transistors, and photo-detectors. [1][2][3][4][5] As usual, GaN lms are grown by metal-organic chemical vapor deposition (MOCVD). [6][7][8] However, it requires a high growth temperature, which leads to high consumptions in both power and cost.…”
Section: Introductionmentioning
confidence: 99%
“…29 It has been reported that chemical reaction/etching by CMP of GaN surface can result in exposing the dislocations created during the original growth process, which are covered during the re-growth process. 15,22,30,31 Recently, Li et al reported the in-plane stress along m-axis is two orders of magnitude higher than that along c-axis on the overgrown semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN epilayer. 29 They have explained that this is due to the dissimilar growth rate and lattice mismatch.…”
Section: X-ray Rocking Curve (Xrc)mentioning
confidence: 99%
“…Ever since high-efficiency p-GaN doping was successfully achieved by Akasaki, 1 GaN-based semiconductors have attracted intense interest due to wide applications for blue and white light emitting diodes (LEDs). [2][3][4] To date, LEDs' luminous efficiency has been much higher than that of lament lamps. However, to meet the market demand for high power lighting and make full use of LEDs' superiorities, luminous efficiency for LEDs still needs indispensable improvement.…”
Section: Introductionmentioning
confidence: 99%